The Impact of Listening to the Tegalan Song “Tolerance” on the Attitude of Religious Moderation - Allyusni, Oni; Basukiyatno, Basukiyatno; Maufur, Maufur (Universitas Pahlawan Tuanku Tambusai, 2025)
This research study aims to determine the form of attitudes and intolerant behaviour, the influence of Tegalan's song “Tolerance” on the attitude of religious moderation and the supporting and inhibiting factors affecting religious moderation. Religious moderation and the supporting and inhibiting factors that affect the effectiveness of the effectiveness of the song “Tolerance” in improving the attitude of religious moderation in Madrasah Tsanawiyah Negeri 3 Tegal. Religious moderation in Madrasah Tsanawiyah Negeri 3 Tegal. Type of This research is a qualitative research that uses research method (field research). The result of This research shows that there are still forms of intolerant attitudes and behaviors such as: Easy judging other people even to the rejection of differences. So that from The existence of this behaviour resulted in the birth of disharmony in the madrasah community as a whole. The effectiveness of the Tegalan song “Tolerance” can also increase moderate attitudes that can indirectly erode the social disharmony that occurs in Madrasah Tsanawiyah Negeri 3 Tegal. Supporting factors for the effectiveness of the song “Tolerance” in improving the attitude of religious moderation is a policy that is supported by all components of the school. All components of the school. While the inhibiting factor is the limited time to integrating songs in formal education programs.